Barriers for blood donation in non-blood donor: a qualitaive study - Mohd Asmawi, Ummi Mohlisi; Osman, Maznah; Said, Norimah; Mohammad, Mariam (Environment-Behaviour Proceedings Journal, 2019)
Donating blood is a noble act that serves a humanitarian cause. This study aims to explore the barriers from donating blood amongst non-donors. Four focus group discussions (FGD) were conducted amongst non-blood donors. The discussions were carried out in the local language, and the verbatim was translated into English. Most of the participants were aware of the importance of donating blood to save other people. Fear is the most factors that hinders them from becoming a blood donor. The participants recommended the use of advertisements that could stir an emotional reaction. Blood banks should hence organise more blood donation campaigns to spread the awareness in the community. Keywords: awareness; blood donation; blood bank; focus group discussion eISSN: 2398-4287 Â© 2019. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v4i10.1622